ASSESSMENT AND EVALUATION IN EFL TEACHING AND LEARNING - Effendy Gultom (Universitas Negeri Padang, 2016)
In general, assessment and evaluation must be done by every EFL teacher. Most teachers conduct a test or examination to measure the students` achievement in EFL teaching and learning. The tests can be either diagnostic or prognostic. The words `test` and `examination` have a considerable amount of overlap of meaning. They may measure someone`s present achievement or delineate his present weaknesses, or they may claim to measure potential. Normally, teachers conduct tests to make assessment and evaluation. The test may be either subjective or objective. In the subjective test, the scoring is impressionistic, not necessarily reliable, dependent to some extent on the marker`s whim or judgment. In the objective test, there is a list of items each with only one correct answer, and the marker`s task is simply mechanical to total the number of `rights` and `wrongs`. An example of a subjective test is the marking of an English essay. An example of an objective test is the multiple choice type of test with the instruction to the students to tick the correct answer. Tests might measure linguistic competence, or they might measure particular skills. Tests can be written or oral. In constructing a test or examination, we need to check the validity in the sense that it measures what it is intended to measure. It is possible for an examination to be reliable but not valid. Reliable means that different examiners award the same marks to the same paper. In general, examinations are more ominous for students than tests. Students might have semester examinations but weekly tests. Examinations sound more serious than tests.